2021
DOI: 10.4049/jimmunol.2000981
|View full text |Cite
|
Sign up to set email alerts
|

Repurposed Tocilizumab in Patients with Severe COVID-19

Abstract: The coronavirus disease 2019 (COVID-19) has caused a global pandemic, resulting in considerable morbidity and mortality. Tocilizumab, an inhibitor of IL-6, has been widely repurposed as a treatment of severely ill patients without robust evidence supporting its use. In this study, we aimed to systematically describe the effectiveness of treatment and prevention of the cytokine storms in COVID-19 patients with tocilizumab. In this multicentered retrospective and observational cohort study, 65 patients with COVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 37 publications
(28 reference statements)
1
31
0
Order By: Relevance
“…Thirdly, every doctor has a different treatment for clinical diagnostic and treatment algorithms, which would allow for adjustment by other factors. 3 , 25 , 26 , 27 In addition, the inclusion of zero‐event trials can sometimes decrease the effect size estimate and narrow the CIs.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, every doctor has a different treatment for clinical diagnostic and treatment algorithms, which would allow for adjustment by other factors. 3 , 25 , 26 , 27 In addition, the inclusion of zero‐event trials can sometimes decrease the effect size estimate and narrow the CIs.…”
Section: Discussionmentioning
confidence: 99%
“…The meta-analysis by Wei et al describes a possible positive effect of tocilizumab, especially for critical patients, and follow-up data of the largest and blinded clinical trials are still being conducted [40]. According to Stone et al, it is not possible to exclude that the treatments decreased the harmful inflammatory syndrome, but there is no evidence of a positive effect: further follow-up trials could clarify the value of this potential effect [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, tocilizumab and sarilumab were proposed as promising therapeutic strategies to reduce mortality in COVID-19, by blocking IL-6 signalling, and ameliorating the deleterious effects of the inflammatory storm ( 20 ). The RECOVERY trial study recently demonstrated the effectiveness of tocilizumab and dexamethasone combined in improving the survival rate and reducing the risk for ventilatory assistance in COVID-19 patients ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…The RECOVERY trial study recently demonstrated the effectiveness of tocilizumab and dexamethasone combined in improving the survival rate and reducing the risk for ventilatory assistance in COVID-19 patients (21).…”
Section: Introductionmentioning
confidence: 99%